2015
DOI: 10.3892/ol.2015.3798
|View full text |Cite
|
Sign up to set email alerts
|

The significance of microRNA-184 on JAK2/STAT3 signaling pathway in the formation mechanism of glioblastoma

Abstract: Glioblastoma is a type of glioma with a relatively higher degree of malignancy that may result in severe intracranial hypertension and focal symptoms. Surgery is the preferred treatment modality. Combination therapy including radiotherapy, chemotherapy, gene therapy, immunotherapy and targeted therapy have also been employed. However, due to the invasiveness and pathogenesis of the disease, such treatments do not yield satisfactory outcomes. The aim of the present study was to examine the expression of microRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Moreover, miRNAs are abnormally expressed in various cancers and closely related with cancer initiation and progression (14)(15)(16). They also act as tumour suppressors or promoters by directly targeting known oncogenes or tumour suppressor genes (17)(18)(19). Therefore, identifying specific miRNAs that play important roles in tumourigenesis and tumour development might provide therapeutic biomarkers for cancer diagnosis, prognosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs are abnormally expressed in various cancers and closely related with cancer initiation and progression (14)(15)(16). They also act as tumour suppressors or promoters by directly targeting known oncogenes or tumour suppressor genes (17)(18)(19). Therefore, identifying specific miRNAs that play important roles in tumourigenesis and tumour development might provide therapeutic biomarkers for cancer diagnosis, prognosis and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, JAK2/STAT3 pathway is deeply involved in the survival and motion of tumor cells [35]. The excessive activation of JAK2 signaling in glioma is accelerated by abnormal signals from upstream regulators [36,37]. This usually involves any gain-of-function mutations or up-regulation of upstream inhibitors, and, on the other hand, any loss-of function mutation or down-regulation of the upstream inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study reported that in vitro proliferation and invasive ability of osteosarcoma U-2OS cells and 143B cells transfected with miR-184 analogue sequence were markedly enhanced, which was consistent with a previous study regarding the regulatory effect of miR-184 on osteosarcoma cell lines ( 21 ). MiR-184 has been demonstrated to promote the proliferation and invasion of glioblastoma ( 38 ). Su et al ( 16 ) reported that miR-184 may function as a tumor suppressor in renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%